Blood and aqueous humor phoenixin, endocan and spexin in patients with diabetes mellitus and cataract with and without diabetic retinopathy - Celik, Fatih; Aydin, Suleyman (Elsevier Science Inc, 2022)
Peptide phoenixin (PNX), endocan (EDC), and spexin (SPX) are associated with diabetes. Therefore, the purpose of this study was to investigate the levels of PNX, EDC and SPX in the blood and aqueous humor (AH) of patient with type 2 diabetes with and without DRP and cataract. 30 type 2 diabetes patients with cataract (DM + C), 30 DRP patient with cataract (DRP + C), 30 non-diabetic patient with only cataract and 30 control participants were enrolled into this study. PNX, EDC, and SPX were measured in blood and AH by ELISA. In patients with DRP + C, the levels of PNX and EDC were significantly higher in both AH and blood samples compared with the group of patients without DRP + C (<0.05). Also, in patients with DM + C, the levels of PNX and EDC were higher in both AH and blood samples compared with the group of patients without DM + C. However, in patients with DRP + C, the levels of SPX were significantly lower in both AH and blood samples compared with the group of patients without DRP + C (<0.05). Also, in patients with DM + C, the levels of SPX were also lower in both AH and blood samples compared with the group of patients without DM + C. These findings suggest that increased PNX, EDC, and decreased SPX amounts in blood and AH of DM + C and DRP + C groups when compared with control and cataract groups show that they might have a role in the pathophysiology of DM + C, especially in the DRP + C.
Keywords: Aqueous humor; Diabetic retinopathy; Endocan; Phoenixin; Spexin